Geothermal Heat Flux Reveals the Iceland Hotspot Track Underneath Greenland - Yasmina M. Martos; Tom A. Jordan; Manuel Catalán; Thomas M. Jordan; Jonathan L. Bamber; David G. Vaughan (Geophysical Research Letters)
Abstract Curie depths beneath Greenland are revealed by spectral analysis of data from the World Digital Magnetic Anomaly Map 2. A thermal model of the lithosphere then provides a corresponding geothermal heat flux map. This new map exhibits significantly higher frequency but lower amplitude variation than earlier heat flux maps and provides an important boundary condition for numerical ice‐sheet models and interpretation of borehole temperature profiles. In addition, it reveals new geologically significant features. Notably, we identify a prominent quasi‐linear elevated geothermal heat flux anomaly running northwest–southeast across Greenland. We interpret this feature to be the relic of the passage of the Iceland hotspot from 80 to 50 Ma. The expected partial melting of the lithosphere and magmatic underplating or intrusion into the lower crust is compatible with models of observed satellite gravity data and recent seismic observations. Our geological interpretation has potentially significant implications for the geodynamic evolution of Greenland.